TOPO - CADASTRAL WORKS PERFORMED FOR THE REGISTRATION IN THE INTEGRATED SYSTEM OF CADASTRE AND REAL ESTATE ADVERTISING OF THE REAL ESTATES FROM UAT JIDVEI, ALBA COUNTY (PANGEEA, 2025)
At this moment, in Romania it is desired the introduction of the general cadastre and with it, the completion of specialized cadastres. The objective of systematic cadastre is the registration into the Integrated cadastre and land book system of the real estates located outside towns, the works beeing initiated by the territorial administrative unit at the cadastral sector level. The theme of this paper is to solve a topical problem in our country, namely: the registration in the Land Book of real estates from a cadastral sector located in the outskirts of UAT Jidvei, through the National Cadastre and Land Book Program (PNCCF). The objective is based on the measurement and free registration of all real estates (land and building), in the integrated system of cadastre and real estate advertising.
Keywords: systematic cadastre; integrated cadastre and land book system